2007
DOI: 10.1097/01.prs.0000278068.99643.8e
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Morbidity of the Frontofacial Monobloc Advancement in Children by the Use of Internal Distraction

Abstract: Internal distraction allows for early correction of respiratory impairment and exorbitism of faciocraniosynostosis, and limits the major risks of frontofacial monobloc advancement. Previous operations performed before the frontofacial monobloc advancement increased its morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
64
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(70 citation statements)
references
References 37 publications
3
64
0
3
Order By: Relevance
“…In general, a significant decrease of OSAS is found after LF III and MB advancement (Holmes et al, 2002;Elwood et al, 2003;Meling et al, 2004Meling et al, , 2006Fearon, 2005;Mathijssen et al, 2006;Arnaud et al, 2007;Nelson et al, 2008;Flores et al, 2009). In nine subjects of the study cohort the outcomes of the upper airway volume measurements correlated to the respiratory outcome.…”
Section: Discussionmentioning
confidence: 88%
“…In general, a significant decrease of OSAS is found after LF III and MB advancement (Holmes et al, 2002;Elwood et al, 2003;Meling et al, 2004Meling et al, , 2006Fearon, 2005;Mathijssen et al, 2006;Arnaud et al, 2007;Nelson et al, 2008;Flores et al, 2009). In nine subjects of the study cohort the outcomes of the upper airway volume measurements correlated to the respiratory outcome.…”
Section: Discussionmentioning
confidence: 88%
“…The mean follow-up was 24 months 21 . ARNAUD et al 2 showed a respiratory improvement measured by oxygen level in 14 of 16 patients with Apert, Crouzon or Pfeiffer syndromes after monobloc with internal distraction. In the severe cases, removal of tracheostomy was possible in 4 of 6 (67%).…”
Section: Discussionmentioning
confidence: 98%
“…10,16 In 1995, Polley et al were the first to describe midfacial advancement by an external distraction device in a newborn with extreme midfacial retrusion. 17 Chin and Toth were the first to use internal distraction devices in maxillofacial applications.…”
Section: Discussionmentioning
confidence: 98%